What do physicians think about the white coat, about patients' view of the white coat, and how empathetic are physicians toward patients in hospital gowns? An enclothed cognition view - Gabay, Gillie; Ornoy, Hana; Deeb, Dana O. (Frontiers in Psychology, 2024)
The receipt of the white coat by medical students is a significant milestone. Extensive research has focused on the white coat, its purity, representation of authority and professionalism, its role in consolidating a medical hierarchy, and the professional status attributed to physicians wearing it. Studies suggest that the white coat is a symbol of medical competence, and patients expect physicians to wear it. Research, however, has paid little attention to what physicians think about their white coat, how they perceive the patient's view of the white coat and the hospital gown, within the patient–physician power asymmetry, which is the focus of the current study. In total, 85 physicians from three Israeli medical centers completed a questionnaire (62% Muslims, 33% Jewish, and 5% Christians; 68% men, ages ranging from 21 to 73 years). Employing the enclothed cognition theory and adopting a within-person approach, we found that the more physicians perceived the white coat as important, the more they attributed a positive view of the white coat to patients and the more they perceived the patient's view of the hospital gown as positive. In addition, the higher the perceived importance of the white coat, the higher the reported empathy of physicians toward inpatients, which is consistent with the hospital's values of care. Interestingly, although medicine is a symbol of protection and care for others, the symbolic meaning of the white coat was potent enough to elicit empathy only when physicians perceived it as important. This study extends the theoretical knowledge on the theory of enclothed cognition in healthcare regarding self-perceptions and professional conduct.